1991
DOI: 10.1021/bi00112a013
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the four hemes of cytochrome c554 from Nitrosomonas europaea by redox potentiometry and optical spectroscopy

Abstract: The electrochemical behavior of tetraheme cytochrome c554 from Nitrosomonas europaea has been studied by thin-layer spectroelectrochemistry, cyclic voltammetry, differential pulse voltammetry, and alternating current voltammetry. Three redox couples were detected. Midpoint potentials for the high-m intermediate-, and low-potential couples are +47, -147, and -276 mV, respectively, from the spectroelectrochemical measurements and +50, -120, and -225 mV, respectively, from the voltammetry measurements. A coulomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 12 publications
6
37
0
Order By: Relevance
“…As HAO has been shown by x-ray crystallographic analysis to exist as a trimer (35), and this multimerization is reasoned to be essential for stabilization and catalytic function, the HAO-Cyt c 554 electron transfer complex is thought to be consistent of 36 hemes. Comparable data regarding reduction potential ranges to that presented here for the membranous c-hemes of S. frigidimarina NCIMB400 have also been obtained for the HAO (36) and Cyt c 554 (37) of N. europea, with the lowest midpoint values noted for these proteins being Ϫ390 and Ϫ226 mV, respectively. Furthermore, x-ray crystallography has revealed a number of structural similarities between the tetraheme core of Cyt c 554 (38) and four of the c-hemes of HAO (35).…”
Section: Figsupporting
confidence: 76%
“…As HAO has been shown by x-ray crystallographic analysis to exist as a trimer (35), and this multimerization is reasoned to be essential for stabilization and catalytic function, the HAO-Cyt c 554 electron transfer complex is thought to be consistent of 36 hemes. Comparable data regarding reduction potential ranges to that presented here for the membranous c-hemes of S. frigidimarina NCIMB400 have also been obtained for the HAO (36) and Cyt c 554 (37) of N. europea, with the lowest midpoint values noted for these proteins being Ϫ390 and Ϫ226 mV, respectively. Furthermore, x-ray crystallography has revealed a number of structural similarities between the tetraheme core of Cyt c 554 (38) and four of the c-hemes of HAO (35).…”
Section: Figsupporting
confidence: 76%
“…Under optimal conditions, their extracts catalyzed ammonia-dependent 02 uptake at rates close to 10% of the rates observed with whole-cell suspensions (48). The extracts were, however, quite unstable: upon storage at 40C, the extracts lost 50% of their AMO activity in 4 h, and when frozen at 20'C, they were stable for only 1 to 2 days. The activity of the extracts was also variable and dependent upon the age and in vivo AMO activity of the N. europaea cells.…”
mentioning
confidence: 72%
“…These studies were expanded to demonstrate that purified, reduced cytochrome c554 could serve as a reductant for the oxidation of ammonia or CO by the membrane fraction, leading to the suggestion that cytochrome c554 may serve as a direct electron donor to AMO (51). Recently, it has been shown that cytochrome c554 will also form a stable complex with and serve as an electron acceptor for purified HAO (3,4 Ba"4CO3 (specific activity = 56 mCi/mmol), obtained from Sigma Chemical Co., St. Louis, Mo., as described previously (19). Unlabelled acetylene was generated in a gasgenerating bottle from calcium carbide (Aldrich Chemical Co., Milwaukee, Wis.) as described previously (18).…”
mentioning
confidence: 99%
“…NH3 + 02+ 2e-+ 2H+ -> NH2OH + H20 Next, hydroxylamine is oxidized to nitrite in a dehydrogenase reaction (2) in the periplasm, which is catalyzed by the multiheme enzyme HAO (15) in concert with the tetraheme electron acceptor cytochrome C554 (3,4):…”
mentioning
confidence: 99%